Review of "The Role of Bacteria in Climate Change: Emissions and Carbon Cycling - Eman Hamza Mohammed (Academia One, 2024)
The accumulation of greenhouse gases has been slowly increasing over time due to various anthropogenic natural processes. These determinants include burning of excess coal, oil, and coal, biodegradation, and biomass burning Currently, climate change and global warming are formidable challenges that nations between people meet. This phenomenon negatively affects many natural processes. It also affected the structure, efficiency, and metabolism of microbial assemblages. It identifies strategies for effectively addressing climate change. For example, microorganisms and other organisms have great potential for mitigation through adaptive responses. They play various roles in preventing and reducing greenhouse gases, especially through nutrient recycling processes. They act constructively as producers or consumers of this gas. This project serves to address environmental hazards from natural and man-made sources. In summary, biogeochemical cycles and climate change should not be interpreted as separate events
Keywords: Bacteria; Climate ChangeEmissions; Mitigation